The impact of intrauterine adhesions on endometrial receptivity in patients undergoing in vitro fertilization-embryo transfer - Ouyang, Yan; Peng, Yangqin; Zheng, Mingxiang; Mao, Yuyao; Gong, Fei; Li, Yuan; Chen, Hui; Li, Xihong (Frontiers in Endocrinology, 2025)
ObjectiveTo clarify whether intrauterine adhesions (IUAs) affect endometrial receptivity (ER) on the day of ovulation and to compare patients with mild and moderate-severe adhesions.MethodsThis prospective cohort study included 592 infertile women with IUAs who underwent frozen-thawed embryo transfer (FET). Patients were divided into groups with or without IUAs; and pregnant and nonpregnant populations based on whether a clinical pregnancy was achieved. The ultrasound ER parameters on the ovulation day were compared. Patients with IUAs were then divided into mild or moderate-severe IUA subgroups according to IUA degree.ResultsThe proportions of patients with Type B plus Type C endometrial morphology (94% vs. 75%, P<0.001), an endometrial thickness≥8mm (97% vs. 81%, P<0.001), an endometrial volume≥2ml (94% vs. 67%, P<0.001), a frequency of endometrial peristalsis≥2 times/min (84% vs. 53%, P<0.001), low subendometrial volume (11.54 ± 2.94 vs. 9.57 ± 2.35, P<0.001) and subendometrial vascularization flow index (VFI) values (2.70 ± 3.10 vs. 2.23 ± 2.23, P=0.033) and a low live birth rate (65% vs. 56%, P=0.039) were significantly higher in the group without IUAs than in the group with IUAs. The group with moderate-severe IUAs had lower proportion of patients with an endometrial thickness≥8mm (73% vs. 89%, P=0.008) and an endometrial volume ≥2ml (58% vs. 78%, P=0.005), a lower frequency of endometrial peristalsis≥2 times/min (42% vs. 65%, P=0.003), and low subendometrial volume (9.22 ± 2.29 vs. 9.97 ± 2.36, P=0.023) and subendometrial flow index (FI) (31.48 ± 3.64 vs. 33.43 ± 4.17, P=0.002) values than the group with mild IUAs; a high antral follicle count (AFC), basal follicle-stimulating hormone (FSH), and anti-Müllerian hormone (AMH) levels and an endometrial thickness≥8mm were independent predictors of clinical pregnancy.ConclusionIUAs can affect ER on the ovulation day and the live birth rate during natural cycles. Moderate-severe IUAs have a greater impact on ER than mild adhesions do; however, if these adhesions are treated properly, they do not have adverse effects on the clinical pregnancy rate. A high AFC, basal FSH and AMH levels and an endometrial thickness ≥8 mm were found to be independent predictors of clinical pregnancy.